Trypanosoma brucei L11 Is Essential to Ribosome Biogenesis and Interacts with the Kinetoplastid-Specific Proteins P34 and P37 - Jaremko, Daniel (mSphere, 2019)
Eukaryotic ribosome biogenesis is an essential cellular process involving tightly coordinated assembly of multiple rRNA and protein components. Much of our understanding of this pathway has come from studies performed with yeast model systems. These studies have identified critical checkpoints in the maturation of the large ribosomal subunit (LSU/60S), one of which is the proper formation and incorporation of the 5S ribonucleoprotein complex (5S RNP). Research on the 5S RNP has identified a complex containing the four proteins L5, L11, Rpf2, and Rrs1 as well as 5S rRNA. Our laboratory has studied the 5S RNP in Trypanosoma brucei, a eukaryotic parasite, and identified the proteins P34 and P37 as essential, parasite-specific members of this complex. We have additionally identified homologues of L5, Rpf2, Rrs1, and 5S rRNA in T. brucei and characterized their roles in this essential process. In this study, we examined the T. brucei homologue of ribosomal protein L11 as a member of the 5S RNP. We showed that TbL11 is essential and that it is important for proper ribosome subunit formation and 60S rRNA processing. Additionally, we identified TbL11 interactions with TbL5 and TbRpf2, as well as novel interactions with the kinetoplast-specific proteins P34 and P37. These findings expand our understanding of a crucial process outside the context of model yeast organisms and highlight differences in an otherwise highly conserved process that could be used to develop future treatments against T. brucei. IMPORTANCE The human-pathogenic, eukaryotic parasite Trypanosoma brucei causes human and animal African trypanosomiases. Treatments for T. brucei suffer from numerous hurdles, including adverse side effects and developing resistance. Ribosome biogenesis is one critical process for T. brucei survival that could be targeted for new drug development. A critical checkpoint in ribosome biogenesis is formation of the 5S RNP, which we have shown involves the trypanosome-specific proteins P34 and P37 as well as homologues of Rpf2, Rrs1, and L5. We have identified parasite-specific characteristics of these proteins and involvement in key parts of ribosome biogenesis, making them candidates for future drug development. In this work, we characterized the T. brucei homologue of ribosomal protein L11. We show that it is essential for parasite survival and is involved in ribosome biogenesis and rRNA processing. Furthermore, we identified novel interactions with P34 and P37, characteristics that make this protein a potential target for novel chemotherapeutics.